Customer satisfaction measurement towards improving project delivery for Jabatan Kerja Raya - Che Mohd. Zain, Nurul Hanani (2015)
Customer satisfaction measurement is one of the crucial factors to ensure that the quality of the services offered meet and fulfill the needs and requirements of the customers. Thus, the aim of this study is to review the current Customer Satisfaction level for JKR and how the customer satisfaction forms are managed in terms of distribution method, approach and design of the forms that contribute to a reliable data to search for the level of customer satisfaction index ratings and which phase(s) of the JKR customer satisfaction that scores the lowest in terms of satisfaction level. The study also introduced a new concept of customer loyalty to the customer satisfaction programme and aim to examine the relationship and the influence between customer satisfaction and customer loyalty for JKR. It is hoped that by having this study will help JKR to improve and increase their performance in the area or project phase(s) that of concern in order to improve its project delivery. The study also reviews the current customer satisfaction data gathering method used by JKR to gather information and feedback on their services provided using questionnaire survey. This study uses both descriptive and inferential statistical method to analyze important characteristics and summarize survey results. A pilot survey of 20 respondents has been conducted to validate the reliability of the questionnaire. Cronbach’s alpha coeficient gathered for each section of the questionnaire is above 0.7. A total of 107 respondents from among 24 ministries and agencies have participated in the survey. Results indicated the need to improve performance related to cost projection, handover procedures and quality assurance. The common feature for the areas of low satisfaction came out in later phases of the construction project. Generally the overall customer satisfaction is also proven to have influence on customer loyalty.